Impact of Product Diversity and International Diversity on Performance in the Global Automotive Industry - Cheraghali, Hamid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
This study examines the relationships between product diversity, international geographical diversity, and company financial performance in the global automotive industry. A sample of the top twenty global automobile manufacturers of 2012 is used to test the hypotheses. ROS has been employed as the performance indicator, while the number of countries in which a company has manufacturing facilities is an indicator of international geographical diversification. Two different measures have been employed as product diversity indicators – a simple model count, and a modified measure of the Herfindahl index. Also, the company’s age and size are used as control variables. According to the analysis of this study, product diversity has a positive and statistically significant impact on financial performance, but international diversity has a nonsignificant negative relationship with performance. This research also uncovers that international diversity has a positive association with product diversity, while the company’s age negatively affects performance and positively impacts product diversity. Keywords: Product Diversity, International Diversity, Financial Performance.

ÖZ : Bu çalışma, küresel otomotiv sektöründe ürün çeşitliliği, uluslararası coğrafi çeşitliliği ve şirketlerin mali performansları arasındaki ilişkileri incelemektedir. 2012 yılında faaliyette olan en büyük yirmi küresel otomobil üreticilerinden oluşan bir örneklemeyi kullanarak bu çalışmanın hipotezleri test edilmiştir. Satış getirisi (ROS) performans göstergesi olarak kullanılmıştır. Bir şirketin üretim tesisleri bulunduğu ülkelerin toplam sayısı ise uluslararası coğrafi çeşitlendirmenin bir göstergesidir. İki farklı yöntemle ürün çeşitliliği göstergeleri ölçülmüştür - birinde sadece toplam araç model sayısı yapılmış ve diğerinde Herfindahl endeksin değiştirilmiş bir versiyonu geliştirilmiştir. Ayrıca, şirketin yaşı ve büyüklüğü kontrol değişkenleri olarak kullanılmıştır. Bu çalışmanın analizine göre, ürün çeşitliliği, finansal performans üzerinde pozitif ve istatistiksel olarak anlamlı bir etkisi vardır, ancak uluslararası çeşitlilik şirket performansı ile anlamlı olmayan ve negatif bir ilişkisi vardır. Bu araştırma aynı zamanda da ürün çeşitliliği ve uluslararası coğrafi çeşitliliği arasında pozitif bir ilişki, ve şirketin yaşı performansı olumsuz etkilediğini ama ürün çeşitliliği üzerinde olumlu bir etkiye sahip olduğunu ortaya çıkarmıştır. Anahtar Kelimeler: Ürün Çeşitliliği, Uluslararası Çeşitliliği, Finansal Performans.
Master of Business Administration in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2014. Supervisor: Assoc. Prof. Dr. Turhan Kaymak.
Keywords: Business Administration; Automobile industry and trade - Diversity; Automobiles - Marketing; Product Diversity; International Diversity; Financial Performance